Formiminotransferase Cyclodeaminase Suppresses Hepatocellular Carcinoma by Modulating Cell Apoptosis, DNA Damage, and Phosphatidylinositol 3-Kinases (PI3K)/Akt Signaling Pathway - Chen, Jiajia (Med Sci Monit, 2019)
BACKGROUND: Formiminotransferase cyclodeaminase (FTCD) is a candidate tumor suppressor gene in hepatocellular carcinoma (HCC). However, the mechanism for reduced expression of FTCD and its functional role in HCC remains unclear. In this study, we explored the biological functions of FTCD in HCC. MATERIAL/METHODS: The expression and clinical correlation of FTCD in HCC tissue were analyzed using TCGA (The Cancer Genome Atlas) and a cohort of 60 HCC patients. The MEXPRESS platform was accessed to identify the methylation level in promoter region FTCD. CCK-8 assay and flow cytometry analysis were used to explore the proliferation, cell apoptosis proportion, and DNA damage in HCC cells with FTCD overexpression. Western blot analysis was performed to identify the downstream target of FTCD. RESULTS: FTCD is significantly downregulated in HCC tissues and cell lines. Low FTCD expression is correlated with a poor prognosis (P<0.001) and an aggressive tumor phenotype, including AFP levels (P=0.009), tumor size (P=0.013), vascular invasion (P=0.001), BCLC stage (P=0.024), and pTNM stage (P<0.001). Bioinformatics analysis indicated promoter hypermethylation can result in decreased expression of FTCD. FTCD overexpression suppressed cell proliferation by promoting DNA damage and inducing cell apoptosis in HCC cells. FTCD overexpression resulted in increased level of PTEN protein, but a decrease in PI3K, total Akt, and phosphorylated Akt protein in HCC cells, suggesting involvement of the PI3K/Akt pathway. CONCLUSIONS: FTCD acts as a tumor suppressor gene in HCC pathogenesis and progression and is a candidate prognostic marker and a possible therapeutic target for this disease.